PENGEMBANGAN BUKU PANDUAN PENDIDIK BERORIENTASI CHEMO-ENTREPRENEURSHIP (CEP) PADA MATERI IKATAN KIMIA SMA\MA KELAS X - siti jamilah; Agus Kamaludin (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
This study aims to develop teacher’s guidebook oriented by Chemo Entrepreneurship on chemical bonding material also analyze its quality by teacher response. This research was a research and development with the 4-D model (define, design, develop, and disseminate) and limited to the develop stage. The data were collected using validation sheets, quality assessment questionnaire sheets and teacher response questionnaire sheets. The results of research showed that the development of Chemo-Entrepreneurship-oriented teacher’s guidebook on chemical bonding material consists of introductions, learning competencies, learning scenarios, and learning assessments. The quality of the developed book obtained the score of 86,11% (Very Good Category) and well positive response on 92,5%.